The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1097/jnn.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

Daily Life Experiences of Patients With a High-Grade Glioma and Their Caregivers

Abstract: The individual and sometimes opposing preferences among patients and their caregivers for prognostic information is a chosen strategy that supports individual needs in managing the HGG trajectory. Patients and caregivers experience a feeling of solidarity, from which shared hope arises; however, this hope needs to be supported by healthcare professionals. Driven by hope, they seek to optimize the therapeutic effect of the oncological treatments by being engaged together in health promoting activities. As sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 44 publications
5
44
0
Order By: Relevance
“…The results of this study support previous work which has shown that a lack of self-awareness, problem-solving skills, or decision-making abilities among patients with brain tumors may limit their ability to recognise their own needs, or to present themselves as better functioning than is actually the case [45,46]. In this study, patients reported being unable to recognise or articulate their own needs, or recall the support services available to address them, which acted as barriers that prevented them getting help.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of this study support previous work which has shown that a lack of self-awareness, problem-solving skills, or decision-making abilities among patients with brain tumors may limit their ability to recognise their own needs, or to present themselves as better functioning than is actually the case [45,46]. In this study, patients reported being unable to recognise or articulate their own needs, or recall the support services available to address them, which acted as barriers that prevented them getting help.…”
Section: Discussionsupporting
confidence: 80%
“…Given these inabilities, clinicians may need to take a greater role in assessing patients' needs and putting plans in place to ensure they receive support. Despite this, some evidence suggests poorer referral processes for this patient group, at least in the area of rehabilitation [45][46][47]. Low referral rates in the presence of problems seem to stem from clinicians' limited knowledge of the benefits of allied health services [45], discomfort discussing brain tumors and their prognosis [47], and beliefs that rehabilitation is not beneficial for persons with poor prognosis [22,48].…”
Section: Discussionmentioning
confidence: 99%
“…Embedded in an existing health care software platform (sundhed.dk) with a fixed design, the BTW was designed and developed based on the professional clinical and scientific knowledge of a multidisciplinary team, as well as the experiences of patients with HGG and their caregivers (Piil et al, 2014a;Diaz et al, 2009).…”
Section: Designmentioning
confidence: 99%
“…There is, however, inconclusive evidence regarding the effects of IBI (Gorlick et al, 2014;Schrader et al, 2014), as this type of intervention is prone to high attrition or non-use (Gorlick et al, 2014;Chiu and Eysenbach 2010). Approximately 90% of all households in Denmark had Internet access in 2013 (Statistics, 2014) and data shows that patients with HGG and their caregivers search for information about their disease on the Internet (Piil et al, 2014a). The Danish population has a high level of familiarity with accessing online services as all official communication with the authorities is digital.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation